CENOZOIC EVOLUTION OF THE SULFUR CYCLE: INSIGHT FROM OXYGEN ISOTOPES IN MARINE SULFATE - Turchyn A.V.; Schrag D.P. (My University, 2006)
We report new data on oxygen isotopes in marine sulfate (δ18OSO4), measured in marine barite (BaSO4), over the Cenozoic. The δ18OSO4 varies by 6‰ over the Cenozoic, with major peaks 3, 15, 30 and 55 Ma. The δ18OSO4 does not co-vary with the δ34SSO4, emphasizing that different processes control the oxygen and sulfur isotopic composition of sulfate. This indicates that temporal changes in the δ18OSO4 over the Cenozoic must reflect changes in the isotopic fractionation associated with the sulfide reoxidation pathway. This suggests that variations in the aerial extent of different types of organic-rich sediments may have a significant impact on the biogeochemical sulfur cycle and emphasizes that the sulfur cycle is less sensitive to net organic carbon burial than to changes in the conditions of that organic carbon burial. The δ18OSO4 also does not co-vary with the δ18O measured in benthic foraminifera, emphasizing that oxygen isotopes in water and sulfate remain out of equilibrium over the lifetime of sulfate in the ocean. A simple box model was used to explore dynamics of the marine sulfur cycle with respect to both oxygen and sulfur isotopes over the Cenozoic. We interpret variability in the δ18OSO4 to reflect changes in the aerial distribution of conditions within organic-rich sediments, from periods with more localized, organic-rich sediments, to periods with more diffuse organic carbon burial. While these changes may not impact the net organic carbon burial, they will greatly affect the way that sulfur is processed within organic-rich sediments, impacting the sulfide reoxidation pathway and thus the δ18OSO4. Our qualitative interpretation of the record suggests that sulfate concentrations were probably lower earlier in the Cenozoic. © 2005 Elsevier B.V. All rights reserved.
Keywords: BARITE; CARBON CYCLE; CENOZOIC; COUPLED BIOGEOCHEMICAL CYCLES; OXYGEN ISOTOPES; SULFATE; SULFUR CYCLE